A PCSK9 variant and familial combined hyperlipidaemia. Issue 12 (15th August 2008) - Abifadel, M; Bernier, L; Dubuc, G; Nuel, G; Rabès, J-P; Bonneau, J; Marques, A; Marduel, M; Devillers, M; Munnich, A; Erlich, D; Varret, M; et al.
Abstract : Background: Our discovery in 2003 of the first mutations of PCSK9 gene causing autosomal dominant hypercholesterolaemia (ADH) shed light on an unknown factor that strongly influences the level of circulating low density lipoprotein cholesterol (LDL-C). PCSK9 gain of function mutations cause hypercholesterolaemia by a reduction of LDL receptor levels, while PCSK9 loss of function variants are associated with a reduction of LDL-C values and a decreased risk of coronary heart disease. Methods and results: We report an insertion of two leucines (p.L21tri also designated p.L15_L16ins2L) in the leucine stretch of the signal peptide of PCSK9 that is found in two of 25 families with familial combined hyperlipidaemia (FCHL). This mutant is associated with high total cholesterol and LDL-C values in these families and is found also in a patient with familial hypercholesterolaemia and her father. Conclusion: PCSK9 variants might contribute to FCHL phenotype and are to be taken into consideration in the study of this complex and multigenic disease with other genes implicated in dyslipidaemia.